Case report: Safety and efficacy of adalimumab in treating difficult-to-treat rheumatoid arthritis in a human immunodeficiency virus-positive patient, one year follow-up - Chen, Jing-Wen; Deng, Guo-Shu; Zhang, Wen-Shuang; Zhang, Ming-Ying; Guan, Tong; Xu, Qiang (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a joint-disabling inflammatory disease associated with the pathology of synovitis. Some patients with RA are difficult to treat, using disease-modifying anti-rheumatic drugs (DMARDs). Biology and targeted synthetic DMARDs (b/tsDMARDs) are options for patients with RA. Acquired immunodeficiency syndrome (AIDS) is an infectious disease caused by the human immunodeficiency virus (HIV). Adalimumab is an anti-tumor necrosis factor therapy commonly used in patients with RA. However, there are no reports or related data on patients with RA-HIV/AIDS treated with adalimumab are available.In this report, we described the first successful case of a 60-year-old HIV-positive woman with difficult-to-treat RA treated with ADA after being screened for hepatitis virus, latent tuberculosis (LTBI), and other infections. She contracted HIV from sexual exposure while on adalimumab therapy. As the patient was resistant to first-line DMARDs, she continued adalimumab along with the initiation of highly active antiretroviral therapy (HAART). The patient was treated with adalimumab therapy for a year; her CD4+ lymphocyte count was normal, HIV-1 RNA decreased, and no new infections were triggered. The patient achieved clinical remission of RA. In conclusion, adalimumab is a safe option for patients with RA-HIV and may slow the progression of HIV infection. Furthermore, HAART has the potential to reduce joint pain and fatigue in patients with difficult-to-treat RA. Conclusions: Adalimumab is a safe option for patients with RA-HIV,and may slow down the progression of HIV infection. The HAART therapy has the potential to reduce joint pain and fatigue in patients with difficult-to-treat RA.